(untitled) (Нелінійні коливання, 2004)
В даній статті досліджється виникнення хаотичної часткової синхронізації в системі глобально зв'язаних відображень. Проводиться аналіз стрктри кластерних зон в області малих значень параметра зв'язк та передмови творення хаотичних атракторів на кластерних многовидах. Знайдено формл зв'язк між трансверсальними та поздовжними числами Ляпнова для траєкторій на многовиді, а також необхідні мови трансверсальної стійкості цих траєкторій. In this paper we investigate the chaotic partial synchronization appearing in a system of globally coupled maps. We analyze the structure of clustering zones for small coupling values eps and the prerequisites for chaotic attractors being formed on cluster manifolds. We obtain the relationship between transverse and longitudinal Lyapunov numbers for a chaotic trajectory and we derive also the necessary conditions for transverse stability of the latter.